SUMBANGAN AL-KHALĪL DALAM PERKEMBANGAN NAHWU ARAB - Pribadi, Moh (Adabiyyāt: Jurnal Bahasa dan Sastra, 2017)
Al-Khalīl was an one of the most important Arabic figures and became the founder of the Bashrah nahw school. Beside nahw, his studies included sharf, and ‘ilm al-aṣwāt. As an expert of nahw, he succeeded in composing nahw terms which include 'āmil, ma'mūl, i'rāb, binā’, ism, and fi'l. The methods he chose to support his theories were simā'i, 'illah, and qiyās. He was the Arab nahw inventor. A harmonizing the real language and the term nahw can be found in his concept.